Aplikasi Penjualan Bahan Bangunan Menggunakan Visual Studio - Al-Qobidh, Arthan Bhakti; Anbar, Ahmad Danyalin (Lembaga Yasin AlSys, 2025)
In the rapidly evolving digital era, online sales applications have become essential solutions for various businesses, including camera stores. This study aims to develop a sales application that facilitates customer transactions while providing convenience for store owners in managing inventory and marketing products. The application is designed with key features such as a product catalog, search and filter options, a shopping cart, promotional notifications, and user reviews and ratings. Aiming to enhance the shopping experience, the application is expected to boost sales and customer loyalty. However, challenges such as intense competition, data security, and customer service quality must be addressed to achieve success. The findings of this study are anticipated to contribute positively to the development of camera store businesses in the digital era.